Workplace transformations in a post pandemic era : new realities to consider and act upon : for managers, policymakers and practitioners in the field - Malka, S. Charles; MacLennan, Helen; Tiell, Robert H. (Emerald Publishing Limited, 2025)
The workplace has remarkably changed in the aftermath of the 2019 pandemic. The transformation is profound and is still evolving. A wave of voluntary resignations unleashed in the wake of Covid-19 negatively affected the business landscape and triggered unprecedented labor shortages. This, in turn, played well into labor unions' hands, leading in 2023 to historical gains for millions of workers across various industries. And while digital technology has enabled remote work for yet more employees than ever before, employers were hard pressed to offer their workers flexible work arrangements. Topping it all, the explosion of AI in the last two years promised to introduce an innovative revolution in our places of work and usher in a new era, albeit contentious, in the marketplace. With the new opportunities that opened up, a host of challenges surfaced, compelling company managers to consider new ways of tackling them. The change in work behavior in the aftermath of the pandemic, coupled with a strong economy and tight labor market in some sectors, are likely to turn the workplace into a collision course between employee and employer. A reset in employer-employee relationships, perceptions, and employment arrangements is today a new must. Transformational leaders are presented with a unique opportunity to make the workplace a much healthier and happier one. Workplace Transformations in a Post Pandemic Era: New Realities to Consider and Act Upon addresses issues that are hotly and publicly debated by practitioners in the field and by policy makers alike. Along with the challenges our places of work currently face, meaningful opportunities for change are also emerging that should not be wasted.
Includes index.
Keywords: COVID-19 Pandemic, 2020-2023 -- Economic aspects.; Business & Economics -- Business Ethics.; Business ethics and social responsibility.; elektronické knihy; electronic books